The Medina Charter and Lessons of Multiculturalism in Contemporary Islamic Politics - Salma, Zakiati; Hidayat, Rahmad; Harahap, Sumper Mulia (Institut Agama Islam Negeri Curup, 2024)
This article aims to analyze the relevance of the multicultural values contained in the Medina Charter within the context of contemporary Islamic politics. The method used in this research is a descriptive qualitative approach, involving a literature review on the Medina Charter and political policies in majority-Muslim countries that adopt pluralistic values. Data collection was conducted through library research, which included reviewing primary texts and academic studies on multiculturalism in Islamic politics. The analysis was carried out using content analysis to understand how the multicultural values in the Medina Charter can be applied in modern politics. The results show that the Medina Charter offers relevant solutions to address the challenges of multiculturalism, particularly in terms of social justice, equal rights, and religious freedom. This research concludes that the values within the Medina Charter can serve as a foundation for political reform in Muslim-majority countries, emphasizing intergroup dialogue and inclusive policies that respect diversity. Thus, the Medina Charter can serve as a model for Islamic politics in the era of globalization, capable of creating a more just and harmonious society.